Case report: Superficial cervicovaginal myofibroblastoma of the cervix with endometrial carcinoma - Zhang, Xiaowei; Huang, Bifei; Du, Junqiang (Frontiers in Medicine, 2023)
Introduction: Superficial cervical vaginal myofibroblastoma is a rare mesenchymal tumor originating from the superficial stroma of the vagina and cervix. Case Presentation: A 53-year-old female patient with endometrial cancer was admitted to the Department of Gynecology in our hospital. She had a history of breast cancer and had been taking toremifene citrate. Radical resection of the endometrial carcinoma was performed at our hospital. A postoperative pathological diagnosis of endometrial adenocarcinoma with superficial cervical vaginal myofibroblastoma was made. The patient continued to receive breast cancer treatment after surgery and was followed up for 23 months. No recurrence or metastasis was observed in relation to the endometrial cancer or the superficial cervical vaginal myofibroblastoma. Conclusions: There is a certain overlap between superficial cervical vaginal myofibroblastoma and other mesenchymal tumors of the female genital tract. Superficial cervical vaginal myofibroblastoma has a good prognosis, and the combination of tissue morphology and immunohistochemistry is helpful for a definite diagnosis.